TRANSFORMASI PEREMPUAN WIRAUSAHA: MEMBANGUN EKONOMI KREATIF BERBASIS GENDER EQUITY UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT BANTUL - Wijayanto, Andhi; Pangastiti, Nuuferulla Kurniantyas; Miladdyan Airyq, Irnin; Widia, Syam (Jurnal Pengabdian Masyarakat Sabangka, 2025)
MSMEs play a crucial role in improving the economic well-being of communities, particularly women, who are key players in the creative economy. However, challenges in business management and product marketing remain barriers for women entrepreneurs in increasing their competitiveness. This community service program aims to empower women entrepreneurs in the Knitting MSMEs in Nogosari II, Bantul Regency, through gender equity-based entrepreneurship training. These activities include training in digital marketing strategies, strengthening managerial capacity, and optimizing the use of creative economy platforms to expand business networks. Over the course of one month, the program will be implemented through outreach, mentoring, and hands-on practice in utilizing digital technology as a marketing and business development tool. With this training, it is hoped that women entrepreneurs in Bantul will be able to increase the productivity and competitiveness of their businesses, thereby contributing to the sustainable economic well-being of the community.